Comparison of Primary Frequency Control Using Two Smart Load Types - Chakravorty,D; Akhtar,Z; Chaudhuri,B; Hui,SYR (IEEE, 2016)
Primary frequency control using smart loads withreactive only compensation (SLQ) has been shown in the past.In this paper, further improvement in frequency regulation isshown using smart loads with a back-to-back converter (SLBC)arrangement. This introduces additional flexibility and thereby,allows independent and wider control over active and reactivepower consumption of the smart load. The improvement infrequency regulation with SLBCs is compared against SLQsthrough two separate case studies on 4-generator, 2-area testsystem and also the 39-bus New-England test system. A futurescenario with reduced system inertia is considered for both casestudies. Unlike previous exercises involving smart loads, in thisstudy a detailed representation is used for both the multi-machinetransmission system and the distribution networks down to themedium voltage (MV) level where the smart loads (SLBC/SLQ)are connected. This avoids the inaccuracies associated with loadaggregation or use of system equivalents wherein the networkconstraints, spatial voltage variations etc. are not capturedproperly.